Da musealização da arte como possibilidade da sua experiência estética. Uma leitura a partir das posições de Valéry, Proust e Theodor Adorno - Bento, Sílvia (CEM – Cultura, Espaço & Memória, 2020)
The present article is devoted to the «musealisation» of art from an aesthetic point of view. By analysing the essay Museum Valéry Proust by Theodor W. Adorno, we propose to consider the process of «musealisation » of art as an effective condition of possibility for its aesthetic experience. The positions on the subject set forth by Paul Valéry in Le problème des musées and by Marcel Proust in A l’ombre des jeunes filles en fleurs, as presented by Adorno, are the touchstone of this article. Accordingly, it is our purpose to discuss the (subjective) experience of the artistic object as its potential «second life» [Zweites Leben], opposed to the processes of cultural neutralisation of such an object. The recent studies on Odilon Redon developed by Dario Gamboni – and his concept of art suggestif, which comprises a remarkable notion of aesthetic experience – will be analysed.